Evaluation of strawberry (Fragaria × ananassa Duch.) runner plants production in Tierra del Fuego (54°48'57"S) and transplant yield perfomance in subtropical areas of Argentina - Miserendino, Eduardo; Kirschbaum, Daniel Santiago; Portela, Jose Antonio (Acta Horticulturae, 2009)
Presentado al VI International Strawberry Symposium The objective of this research was to evaluate the feasibility of producing fresh plants in Tierra del Fuego (TDF) with the aim of digging plants in early fall and establishing them in subtropical strawberry growing regions of Argentina. Due to the extreme climatic conditions of TDF, plant propagation is only possible under walk-in tunnels. A trial with Chandler and Camarosa planted on black polyethylene covered beds under walk-in tunnels was conducted in the 2004-2005 nursery season using drip irrigation. Two rows of mother plants were set in the center of the beds (180 cm wide), with in-row and between-row spacings of 30 cm and 40 cm, respectively. Mother plants were established in late spring. Chandler produced 30.8 ± 10.0 daughter plants per mother plant, 66% corresponding to commercial plants (crown diameter ≥0.7 cm). Daughter plants of both Chandler and Camarosa were sent to fruiting fields in Famaillá (27°03 00 S) and Bella Vista (28°30 00 S) on April 1st. They were classified by crown diameter (≥10 mm, and <10 mm). Yields ranged from 527 to 865 g per plant. High early fruit production was observed. Stolon and daughter plant production per mother plant were also evaluated in the nursery. Four types of stolons per mother plant were detected according to their cronological order of appearance: I, II, III and IV. The quantity of each stolon type per mother plant was 1.97 (I), 2.68 (II), 3.89 (III) and 3.13 (IV). The number of daughter plants per each stolon type was 6.8 (I), 4.6 (II), 2.2 (III) and 1.0 (IV). We believe this is a very promising research line for getting transplants with high early fruit production potential for subtropical regions of South America. EEA Esquel Fil: Miserendino, Eduardo. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Esquel. Agencia De Extensión Rural Esquel; Argentina Fil: Kirschbaum, Daniel Santiago. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación ...